Social transformation: In North Western India During the 20th Century - Singh, Chetan. (ed.) (New Delhi Manohar, 2010)
More than 150 years after the mid-19th century, northwestern India underwent a degree of social transformation that was impressive. Unraveling the complex nature of the processes underlying this remarkable change, this book reveals diverse modes of resistance and response, especially in the Punjab, to a colonial ideology that sought to institute a subtle, yet powerful, forms of social control. After Independence, the much celebrated Green Revolution drew the peasantry of northwestern India into the vortex of economic trends that had unexpected and far-reaching consequences, which are today a matter of great concern. Long-term social currents that had been stirring rather slowly in the region gained momentum. As a result, the process of societal change, started earlier began to strain against the restrictive fabric of the traditional social order. Social Transformation in northwestern India endeavours to explain the multidimensionality of change that is so characteristic of the region. This book would be of interest as much to the social scientist and the policy maker as to the journalist and the lay reader.
Keywords: North-West India-Social transformation